Mothering in the Aftermath of Forced Marriage and Wartime Rape: The Complexities of Motherhood in Postwar Northern Uganda - Denov, Myriam; Green, Amber; Lakor, Atim Angela; Arach, Janet (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
During northern Uganda’s civil war (1986-2007), the abduction, forced marriage, and impregnation of females was a key military strategy of the Lord’s Resistance Army (LRA). The LRA abducted an estimated sixty thousand children—30 percent of which were girls—who were used as combatants, porters, domestic workers, and were forced to marry male commanders. Roughly ten thousand of these abducted girls became pregnant from sexual violence, and gave birth to two or more children each. This paper explores the realities of mothering in the aftermath of wartime sexual violence. Drawing upon interviews with a sample of twenty-seven northern Ugandan mothers who bore children as a result of wartime rape, the paper explores the ambivalence and complexities of mothering in the postwar period—including sexual violence, pregnancy and mothering during LRA captivity, as well as stigma and rejection, and changing family structures in the postwar period. The paper highlights the ways in which war shapes and informs all aspects of mothering—both during and following the conflict—and how it alters how women come to understand their life stories as part of the motherline. We conclude with key implications for service provision and policy.